The Theory of the Demand for Health Insurance - John A. Nyman (University of Minnesota, Center for Economic Research, 2001)
Conventional theory holds that moral hazard - the additional health care purchased as a result of becoming insured - is an opportunistic price response and is welfare-decreasing because the value of the additional health care purchased is less than its costs. The theory of the demand for health insurance presented here suggests that moral hazard is primarily an income transfer effect. In an estimation based on parameters from the literature, the value of moral hazard consumption is found to be 3 times greater than its costs, suggesting that income transfer effects dominate price effects and that moral hazard is welfare-increasing.
Keywords: 330; health insurance; moral hazard; income transfer effect; Krankenversicherung; Konsumtheorie; Versicherungsökonomik; Gesundheitsökonomik; Theorie; USA